Multicenter study of HPC coated p48 and p64 flow diverters for treatment of intracranial aneurysms under dual antiplatelet therapy - Görtz, Lukas; Weyland, Charlotte S.; Nikoubashman, Omid; Buerkle, Franziska; Beukelaer, Frédéric De; Siebert, Eberhard; Gronemann, Christian; Hohenstatt, Sophia; Dorn, Franziska; Bohner, Georg; Wiesmann, Martin; Ridwan, Hani; et al. (Interventional neuroradiology, 2025)
Objective Phenox flow diverters (p64 and its smaller vessel variant p48) represent an established treatment option for intracranial aneurysms. This study evaluates the safety and efficacy of the new generation of these devices with an additional antithrombotic surface coating (HPC).Methods Consecutive patients treated between 2020 and 2023 at three institutions were retrospectively reviewed for aneurysm characteristics, procedural details, complications, and angiographic outcomes.Results Sixty-one patients (mean age 56 years) were treated for 61 aneurysms. The mean aneurysm size was 8.3 +/- 4.9 mm, 12 (19.7%) were ruptured, 16 (26.2%) were recurrent after previous treatment, 10 (16.4%) were located in the posterior circulation, and 7 (11.5%) had nonsaccular morphology. All procedures were technically successful, with a single device sufficient in 60/61 (98%) cases. Delivery problems included device twisting in one case and incomplete proximal opening in another. Additional angioplasty was performed in 3/61 (4.9%) procedures and additional coiling in 4 (6.6%). There were 3 (4.9%) major events (1 thromboembolic ischemic stroke, 1 fatal intracranial hemorrhage, and 1 delayed aneurysm rupture) and 6 (9.8%) minor strokes. Follow up at a mean of 6 months showed complete occlusion in 33/42 (79%) aneurysms, neck remnants in 5 (12%), and aneurysm remnants in 4 (10%).Conclusions The results demonstrate comparable acceptable complication rates and angiographic results of the Phenox HPC, which are similar to other flow diverters. Long-term and comparative studies are needed to evaluate the full potential of these devices.
Online veröffentlicht am 24. Februar 2025
Gesehen am 23.10.2025